Analisis Antropometri dan Daya Tahan VO2Max Peserta Ekstrakulikuler Bolavoli Putri SMAN 1 Talun Blitar - Prasetya, D D; Sulistyorini, Mrs (Performance, 2020)
Abstract: The purpose of this study was to determine anthropometry and endurance levels in female volleyball extracurricular students at SMAN 1 Talun Blitar. The research method used is the survey method. The subjects used were female volleyball extracurricular students at SMAN 1 Talun Blitar. The results of this study are the results of anthropometric percentage and VO2Max endurance of volleyball female extracurricular students of SMAN 1 Talun Blitar, then the results of the study can be a benchmark of anthropometry and VO2Max durability for trainers to know team weaknesses and improve anthropometry and durability VO2Max team to be better. Keywords: Anthropometry, VO2Max Endurance, Volleyball Abstrak: Tujuan penelitian ini adalah mengetahui antropometri dan tingkat daya tahan pada siswa ekstrakulikuler bolavoli putri SMAN 1 Talun Blitar. Metode penelitian yang di gunakan yaitu metode suvei. Subjek yang digunakan adalah siswa ekstrakulikuler bolavoli putri SMAN 1 Talun Blitar. Hasil dari penelitian ini adalah hasil berupa data presentase antropometri dan daya tahan VO2Max siswa ekstrakulikuler bolavoli putri SMAN 1 Talun Blitar, kemudian hasil dari penelitian bias menjadi patokan antropometri dan daya tahan VO2Max untuk pelatih agar mengetahui kelemahan tim dan meningkatkan antropometri dan daya tahan VO2Max tim agar lebih baik. Kata kunci: Antropometri, Daya tahan VO2Max, Bolavoli